Analysis of Guest Satisfaction towards the Quality of Bartender Services - Agus Martha Di Nugraha; Ni Luh Eka Armoni; I Nyoman Winia; I Gede Mudana (International Journal of Glocal Tourism, 2020)
Purpose: This research is to determine the level of guest satisfaction with bartender services and efforts to increase guest satisfaction at a 5 star hotel bar in Jimbaran tourist area, Badung, Bali, Indonesia. Research methods: Data are obtained by distributing questionnaires to 50 respondents. The data were then processed by SERVQUAL and Important-Performance Analysis techniques presented with Cartesian Diagrams. Findings: The guest satisfaction with bartender services at the hotel bar as a whole is high indicated by the act that a positive SERVQUAL score gap was more than the negative SERVQUAL score gap Implications: The hotel bar needs to improve the quality of its bartender services, such as coordination between the bartender and waiter/waitress so that there is no delay in the process of service to guests.